Pengaruh Pemangkasan Pucuk Batang Utama dan Umur Panen Terhadap Hasil Benih Kedelai (Glycine max (L.) Merr.) 'Mallika' - , MUHAMMAD SIDIQ FATWARIZA, Ir. Setyastuti Purwanti, MS. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The research aims were 1) to determine the effect of main stem tip pruning and harvesting time to the seed yield of black soybean, 2) to determine the interaction effect of main stem tip pruning and harvesting time to the yield and quality of black soybean seed and 3) to determine the optimal harvesting time of âMallikaâ black soybean. The research was conducted at Nogotirto Village, Gamping District, Sleman Region, DIY Province in May-September 2012. The research was conducted in randomized complete block design (RCBD) factorial with 3 blocks as replication. The first factors were pruning, namely main stem tip pruning at 2 weeks after planting and without pruning. The second factors were harvesting time, namely 85, 87, and 90 days after planting. The observations were done on several variables of growth, seed yield and quality of âMallikaâ soybean. Data were analyzed with Analysis of Variance (ANOVA) at 5% level, and continued with Duncan's Multiple Range Test (DMRT). The relationship patterns among the parameters were determined using correlation analysis. The results showed that there was no interaction effect between main stem tip pruning and harvesting time of âMallikaâ soybean to the yield and quality of seed, except in the hypothetical vigor variable. Pruning significantly increases the quantity of black soybean seed yield per hectare, but the seed quality remains the same with the seeds of black soybean produced by crops that were not pruned. Harvesting time does not affect the seed quantity and quality of black soybean produced, including seed hypothetical vigor.